Traumatic Brain Injury, PTSD, and Current Suicidal Ideation Among Iraq and Afghanistan U.S. Veterans. Issue 2 (17th March 2014) - Wisco, Blair E.; Marx, Brian P.; Holowka, Darren W.; Vasterling, Jennifer J.; Han, Sohyun C.; Chen, May S.; Gradus, Jaimie L.; Nock, Matthew K.; Rosen, Raymond C.; Keane, Terence M.
Abstract: Suicide is a prevalent problem among veterans deployed to Iraq and Afghanistan. Traumatic brain injury (TBI) and psychiatric conditions, such as posttraumatic stress disorder (PTSD), are potentially important risk factors for suicide in this population, but the literature is limited by a dearth of research on female veterans and imprecise assessment of TBI and suicidal behavior. This study examined 824 male and 825 female U.S. veterans who were enrolled in the baseline assessment of the Veterans After‐Discharge Longitudinal Registry (Project VALOR), an observational registry of veterans with and without PTSD who deployed in support of the wars in Iraq and Afghanistan and were enrolled in the Veterans Affairs healthcare system. Results indicated that current depressive symptoms, PTSD, and history of prior TBI were all significantly associated with current suicidal ideation (Cohen's d = 0.91, Cramers' Vs = .19 and .08, respectively). After adding a number of variables to the model, including psychiatric comorbidity, TBI history was associated with increased risk of current suicidal ideation among male veterans only (RR = 1.55). TBI is an important variable to consider in future research on suicide among veterans of the wars in Iraq and Afghanistan, particularly among male veterans.